The Classifications of Expressions in the Story "Dakhshat" of Abdullah Kahhor (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Phrasal verbs are of great importance in stories and literature because they often convey nuances and emotions that single word verbs may not capture.They can add depth to character interactions,set the tone, create more vivid narrative. Additionally, using phrasal verbs can contribute to a more conversational,dynamic writing style, making the story more engaging for readers.This article attempts to analyze expressions within the story titled "DAKHSHAT".